2021
DOI: 10.1177/15500594211019917
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Sensorimotor Rhythm During Motor Attempt/Imagery and Upper-Limb Motor Impairment in Stroke

Abstract: Motor attempt (MA)/motor imagery (MI)-based brain–computer interface (BCI) is a newly developing rehabilitation technology for motor impairment. This study aims to explore the relationship between electroencephalography sensorimotor rhythm and motor impairment to provide reference for a BCI design. Twenty-eight stroke survivors with varying levels of motor dysfunction and spasticity status in the subacute or chronic stage were enrolled in the study to perform MA and MI tasks. Event-related desynchronization (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
(69 reference statements)
1
12
0
Order By: Relevance
“…Thus, some covariates can affect the results, especially mental stages, and age. Expect that, we reached similar results compared to previous study [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, some covariates can affect the results, especially mental stages, and age. Expect that, we reached similar results compared to previous study [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…The α-ERD has been observed not only during the elaboration of stimuli belonging to different sensory modalities (i.e., sensory-related α-ERD) but also during various mental tasks (i.e., task-related a-ERD) [ 30 ]. We also found that there was a positive correlation between the Fugl-Meyer assessment of upper limb (FMA-UE) and ERS in the unaffected hemisphere in MI tasks, and there were negative correlations between FMA-UE scores and ERD in both hemispheres [ 31 ] in MA task. However, the relationship between the different motor tasks performed by the various hand function of a stroke patient and the brain activation is still unclear.…”
Section: Introductionmentioning
confidence: 84%
“…In the previous study (Chen et al, 2021), we tried to explore the relationship between sensorimotor rhythm and upper limb motor impairment (motor dysfunction and spasticity) in MA and MI tasks. It suggests that motor dysfunction may be more correlated to ERS in the MI task and to ERD in the MA task while spasticity may be more correlated to ERD in the MA task.…”
Section: Relationship In Brain-computer Interface Accuracies and Event-related Desynchronization Of Motor Attempt And Motor Imagery Tasksmentioning
confidence: 99%
“…In the same year, we compared the differences between motor attempt and motor imagery tasks, which are commonly used in a closed-loop BCI system (Chen et al, 2021). In 2022, we further demonstrated the relationships between sensorimotor rhythm during motor attempt/imagery tasks and upper limb motor impairment in stroke (Chen et al, 2022), which may support the clinical application of the closed-loop BCI system. To sum up, we have explored the closed-loop application of BCI in both the clinic and brain region activations and will move forward to examining its closed-loop brain mechanism.…”
Section: Introduction Concept and Development Of The Theory Of Centra...mentioning
confidence: 88%